Relationship Building as a Marketing Strategy: A Conceptual Guide for African Exporters - Phambuka-Nsimbi, Catherine (Indian Journal of Marketing, 2011)
Exporting has been one of the fastest growing economic activities around the world during the past two decades and has been fuelled by the world market liberalization and global competition. In fact, exporting is considered to be an important factor contributing to the maintenance of economic growth and prosperity. Specifically, from a macro perspective, exporting creates jobs, contributes to a balance of trade, increases national productivity, helps raise the standards of living or quality of life of a country’s population and provides currency stability. From a micro perspective, Leonidou proposed benefits that include generating business funds for company reinvestment and growth, diversifying company business across different markets, enhancing product innovation due to different foreign market needs, improving utilization of production capacity where the domestic market could not possibly absorb a firm’s full production capacity, developing superior management capabilities as the management deals with different needs and enhancing both - the firm’s sales and financial performance. This paper reviews extant literature of exporter-distributor relationships to identify the benefits and challenges associated with such relationships in an attempt to provide African exporters with the necessary insights on how they could also benefit from tying up with their overseas distributors. The paper emphasizes that exporter-distributor relationships can help improve export performance in Africa, where most countries are still grappling trade deficits and lack export diversity. Africa’s share in global markets is quite small, accounting for 2.1 percent in 2002 compared to 4.1 percent in 1980.